EXPLORING THE PERCEPTIONS OF HEALTHCARE PROFESSIONS OF ADVERSE EVENTS REPORTING AND THEIR IMPACT ON PATIENT SAFETY - Sahar A. Alharbi; Hayat N. Alshammari; Rania A. Sharaf; Haneen S. Barnawi; Amani N. Alturaifi; Zahra A. Alawami (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Adverse event reporting is an integral element for quality and patient safety, particularly in a multidisciplinary environment such as a tertiary setting. This qualitative study sought to delve into the barriers and facilitators to reporting adverse events from the perspective of nurses, pharmacists, allied personnel and physicians. Categories of factors which facilitated or deterred reporting such as supportive leadership and training as well as fear of blame and lack of time emerged from the semi structured interviews and focus group discussions. The participants held conflicting opinions with regard to the electronic health record system of the hospital, indicating a need for user friendly design and appropriate feedback systems. The report highlights deficiencies in the reporting culture and practices and attempts to suggest solutions to them including fostering a non-punitive culture, developing reporting systems that are more user friendly and encouraging collaborative working. The results of this study provide pathways to improving patient safety in a complex healthcare system.